Breast Cancer Development in a Transgender Male Receiving Testosterone Therapy. (31st December 2018) - Barghouthi, Nadia; Turner, Jennifer; Perini, Jessica
Abstract : Context . To describe a case of invasive ductal carcinoma of the breast in a transgender male receiving testosterone therapy for gender-affirming treatment. Case Description . A 28-year-old transgender male receiving intramuscular testosterone was found to have a breast mass on ultrasound after self-exam revealed a palpable breast lump. Ultrasound-guided breast biopsy revealed estrogen receptor/progesterone receptor (ER/PR) negative, human epidermal growth factor receptor-2 (HER-2) positive, invasive ductal carcinoma of the left breast. He underwent neoadjuvant and adjuvant chemotherapy along with bilateral mastectomy. At patient request, his testosterone injections were permanently discontinued. Conclusion . Fewer than 20 cases of breast cancer in transgender male patients have been reported in medical literature. While studies have shown increased risk of breast cancer in postmenopausal women with higher testosterone levels, data regarding premenopausal women is conflicting and little is known about breast cancer risk in transgender individuals receiving gender-affirming hormone therapy (GAHT), with inconclusive results regarding correlation between testosterone therapy and breast cancer. More research is required to evaluate whether a possible increased risk of breast cancer exists for transgender men receiving gender-affirming therapy.